Sarawak Election Commission / Eda Suraya Sahari - Sahari, Eda Suraya (Universiti Teknologi MARA, Sarawak, 2013)
Election Commission of Malaysia or also known as Suruhanjaya Pilihan Raya (SPR) is a commission set up for the purpose of regulating and conducting elections in Malaysia. Its establishment is mandated by Article 114 of the Constitution of Malaysia. The Election Commission falls under the purview of the Prime Minister's Department (Wikipedia, 2013). SPR is an organization to assist the government in managing and implementing the process of election in Malaysia. SPR will act as a bridge for the existing government and opposition party. This is because SPR will provides everything that needed before, during and after the election. In other word, SPR will be the organization to make preparation before the election will be held. During the day of election, SPR will also be the one who manage the anything that needed (including counting of votes). After the election, SPR will be accountable to answer on any decision that has been made.